Human papillomavirus vaccination coverage among men who have sex with men—National HIV Behavioral Surveillance, United States, 2017. Issue 47 (3rd November 2020) - McClung, Nancy; Burnett, Janet; Wejnert, Cyprian; Markowitz, Lauri E.; Meites, Elissa; ,
Highlights: We evaluated HPV vaccination in 2017 among 10, 381 U.S. men who have sex with men. 17.9% of all MSM and 32.8% of MSM aged 18–26 reported receiving ≥ 1 HPV vaccine. Coverage among MSM aged 18─26 doubled since 2014 and was six-fold higher than 2011. Most MSM aged 18─26 were not vaccinated against HPV, even those living with HIV. Abstract: Men who have sex with men (MSM) are at high risk for infections and diseases caused by human papillomavirus (HPV), many of which are vaccine-preventable. In the United States, routine HPV vaccination has been recommended for adolescent males since 2011. This analysis evaluated self-reported receipt of ≥ 1 HPV vaccine dose by age group and HIV status among adult MSM using 2017 data from National HIV Behavioral Surveillance (NHBS) and compared the proportion vaccinated to prior years. Among 10, 381 MSM aged ≥ 18 years, 17.9% of MSM overall and 28.4% of MSM living with HIV reported any HPV vaccination. Among 2, 482 MSM aged 18–26 years, 32.8% overall and 51.3% living with HIV reported HPV vaccination. Since 2011, the proportion of MSM aged 18–26 years reporting HPV vaccination has increased over six-fold. As vaccinated adolescents age into young adults, coverage will continue to increase overall, including among MSM.